A design of degree distribution for systematic fountain codes - Liang Chen; Limin Meng; Zhijiang Xu; Jiangxin Zhang; Wei Jiang (Proceedings - IEEE International Conference on Networks, 2013)
This paper proposes a new degree distribution for systematic fountain codes by analyzing the property of systematic code. The erasure probabilities are also taken into consideration during the design. The simulation shows that the new distribution needs less encoding packets to recover all the source packets, has rapid constringency speed, and its performance is not very sensitive to the erasure probabilities.